Performing Magic on the Western Stage
XIII, 240 p. 5 illus.
Keywords: Performing Magic on the Western Stage examines magic as a performing art and as a meaningful social practice, linking magic to cultural arenas such as religion, finance, gender, and nationality and profiling magicians from Robert-Houdin to Pen& Teller.